Strategi Guru Pendidikan Agama Islam dalam Menumbuhkan Nilai-Nilai Religius - Inco, Busra; Rofiq, Muhammad Husnur; Shonhadji; Iskandar (Chalim Journal of Teaching and Learning, 2022)
Instilling religious values ​​from an early age in minority areas is very important, considering the challenges in minority areas are very difficult due to many factors that become obstacles, so the role of education through Islamic religious education teachers is needed to cultivate these religious values. This study aims to explore the strategies of Islamic religious education teachers in cultivating religious values ​​and analyze the strategies of Islamic religious education teachers at MA Hidayatullah Baar Marotauk, East Nusa Tenggara. The method used to answer the objectives of this research is to use qualitative research with an ethnographic approach, using primary data sources obtained through interviews with school principals and Islamic religious education teachers at MA Hidayatullah Baar Marotauk, East Nusa Tenggara. Furthermore, the data obtained is checked for validity, which aims to be scientifically justified. The research results from the teacher's strategy found that two important factors influenced the strategy of Islamic religious education teachers, namely internal factors and external factors. Internal factors are from within the school, while external factors come from outside, such as the environment and family.